Going slow to go fast: Public response and engagement in renewable energy projects - Boudet, H.; Hazboun, S.; Haggett, C.; Batel, S. (Nature Reviews Clean Technology, 2025)
Ambitious targets for renewable energy deployment have run into the reality of local opposition, leaving government officials, developers and the broader climate movement with questions about project siting. A robust field of inquiry in energy social science has developed to analyse public opinion and social acceptance of renewable energy. In this Review, we chart transitions in this field from analysing public support and opposition, to explaining community response to specific projects, and finally to elucidating critical perspectives and a just transition. Although Indigenous engagement with renewable energy development is becoming better recognized, it remains under-represented in energy social science. Most renewable energy development is brought forth under the neoliberal capitalist model; alternative models need to be discussed and materialized. Any engagement efforts should now take on a renewed sense of urgency given the broader trends of misinformation, distrust of institutions and populism. Offshore renewable energy projects (such as offshore wind) not only elicit responses similar to onshore energy but often amplify these dynamics, making engagement even more critical to ensure just and effective siting practices. Engagement, equity and speed — although often thought to be contradictory — are inextricably linked. Effectively engaging communities with the renewable energy transition means ‘going slow to go fast’ to allow energy transitions and equity to work in concert. This work will require making changes to projects as a result of concerns rather than dismissing such concerns, building trust and being realistic about timetables and potential community impacts.